
用乘法公式计算
(x-2y)的平方-(x+2y-3)的平方=「(x-2y)的平方-(2x-y)的平方」(x的平方+y的平方)=2(5x-4y)(-5x-4y)的平方-3(1\3x-3\2...
(x-2y)的平方-(x+2y-3)的平方=
「(x-2y)的平方-(2x-y)的平方」(x的平方+y的平方)=
2(5x-4y)(-5x-4y)的平方-3(1\3x-3\2)的平方=
(x-3)(x-2)+(x-5)(x-6)=
要过程 展开
「(x-2y)的平方-(2x-y)的平方」(x的平方+y的平方)=
2(5x-4y)(-5x-4y)的平方-3(1\3x-3\2)的平方=
(x-3)(x-2)+(x-5)(x-6)=
要过程 展开
展开全部
(x-2y)^2-(x+2y-3)^2=(x-2y-x-2y+3)*(x-2y+x+2y-3)=(3-4y)(4x-3)
[(x-2y)^2-(2x-y)^2]*(x^2+y^2)=(x-2y-2x+y)(x-2y+2x-y)(x^2+y^2)=-3(x-y)^2(x^2+y^2)
会写两题
[(x-2y)^2-(2x-y)^2]*(x^2+y^2)=(x-2y-2x+y)(x-2y+2x-y)(x^2+y^2)=-3(x-y)^2(x^2+y^2)
会写两题
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询